Pengetahuan Mahasiswa Fakultas Ilmu Kesehatan Universitas Muhammadiyah Surakarta Tentang Penerapan Metode Diet Yang Baik Bagi Kesehatan - Ulfia Fitriyani; Nur Hidayati, Intan; Sukmawati, Maya; Puspitasari, Nita; Salsabiila Sayida Rohma, Annisa; Warajati Kisnawaty, Sudrajah (Kabar Gizi Indonesia, 2023)
The behavior of achieving ideal body weight and shape is one method for controlling weight. We can apply this weight control behavior by dieting behavior. This study aims to describe the knowledge of students of the Faculty of Health Sciences, University of Muhammadiyah Surakarta about the application of good diet methods for health. Qualitative research methods with a case study approach. The results of this study, students already know the meaning of diet, most students have the habit of eating 3x a day but there are still students who skip meals. Students apply the low-calorie diet method as much as 62.5% and do a low-fat diet 37.2% in terms of nutritional status 75% of students have normal nutritional status, 12.5% ​​undernutrition status, 12.5% overnutrition status and most students do regular physical activity. It can be concluded that most of the respondents already know about the knowledge or understanding of diet. Perform regular physical activity and most respondents have normal nutritional status. However, in implementing the diet, there are still students who still skip meals.